Avaliação ultrassonográfica da espessura da pele de recém-nascidos e sua relação com a cronologia gestacional - Gabriela Luiza Nogueira Vitral (2017)
Introduction: Gestational chronology is the most important marker of newborn survival. The uncertain of the information can result in neonatal risks, besides leading to problems in the classification of the neonate in growth curves and to modify a proportion of preterm infants. Currently, with the advancement of obstetric and neonatal technologies, new markers that cover the chronology of human pregnancy are demanded. It is believed that the thickness of the neonatal skin is one of the evolutionary parameters with the potential to estimate the chronology of pregnancy. The thickness of the human skin can be obtained safely and non-invasively through ultrasound examination. Objective: To verify if the thickness of the neonatal skin measured by ultrasonography is able to estimate the gestational age at birth, considering the profiles of fetal growth in the measurements of the skin layers. Methods: Cross-sectional observational study in which measurements of skin thickness were obtained by ultrasound examination in 198 neonates with gestational age between 25 and 42 weeks. Evaluation of the skin on the forearm and foot was performed on the first day of life. The thicknesses of the skin layers were compared between neonates with adequate weight (AIG), small (SGA) and large (GIG) for age, according to the Intergrowth-21st curve, using the ANOVA test. The association between skin thickness and the estimated gestational age was verified by regression models. Results: There was no influence of the fetal growth profiles on epidermal thickness (p = 0,903, p = 0,431), dermal (p = 0,194, p = 0,496), total skin (p = 0.192, p = 0.515) and dermis / epidermis ratio (p = 0.239, p = 0.540), for forearm and foot, respectively. The best model to correlate skin thickness with gestational age was obtained with the measurement of the epidermis in the forearm, which assumed quadratic function, r = 0.607, R2 = 0.369 (p <0.001). Conclusion: The study indicates a new opportunity to relate gestational age to neonatal skin layers at birth since there was no influence of fetal growth profiles.